Forced convection to laminar flow of liquid egg yolk in circular and annular ducts - Bernardi, M.; Silveira Jr., V.; Telis, V. R. N. [UNESP]; Gabas, A. L.; Telis-Romero, J. [UNESP] (Brazilian Society of Chemical Engineering, 2009)
The steady-state heat transfer in laminar flow of liquid egg yolk - an important pseudoplastic fluid food - in circular and concentric annular ducts was experimentally investigated. The average convection heat transfer coefficients, determined by measuring temperatures before and after heating sections with constant temperatures at the tube wall, were used to obtain simple new empirical expressions to estimate the Nusselt numbers for fully established flows at the thermal entrance of the considered geometries. The comparisons with existing correlations for Newtonian and non-Newtonian fluids resulted in excellent agreement. The main contribution of this work is to supply practical and easily applicable correlations, which are, especially for the case of annulus, rather scarce and extensively required in the design of heat transfer operations dealing with similar shear-thinning products. In addition, the experimental results may support existing theoretical analyses.
Keywords: Egg yolk; Heat transfer; Laminar flow; Nusselt number